Isolation and bioactivity of chemical constituents from Zingiber cassumunar roxb. and Aglaia oligophylla Miq. - Azid, Mohd Zulkhairi (2012)
Zingiber cassumunar Roxb. (Zingiberaceae) or locally known as “Bonglai” among Malay is traditionally used as medicines to treat, skin disease, inflammation and as one of the component in herbal spices. From the isolation worked on the rhizomes of Zingiber cassumunar, five compounds isolated were elucidated as cis-3-(3',4'-dimethoxyphenyl) -4-[(E)-3''',4'''-dimethoxystyryl]cyclo-hex-1-ene (21), (E)-4-(3',4'-dimethoxyphenyl)but-3-en-1-ol (12), 3,4-dimethoxybenzoic acid (29), 8-(13,14-dimethoxyphenyl)-2-methoxynaphto-1,4-quinone (20), and beta-sitosterol (30). Aglaia oligophylla Miq. belongs to the Meliaceae family which is a large tree up to 25 meter high and locally is known as “Bekak”. Aglaia species have received a lot of attention lately due to its strong insecticidal and cytotoxic activity. Phytochemical studies on stem bark of Aglaia oligophylla has afforded dammarane acid type of compounds, namely 20S,24R-epoxy-25-hydroxy-2-methoxy-2,3-secodammarane-3-oic acid (77) and 20S,24S-epoxy-25-hydroxy-2-methoxy-2,3-secodammarane-3-oic acid (78) while separation work from the trunk of Aglaia oligophylla successfully isolated one compound identified as silvaglin A (47) along with beta-sitosterol (30). Compounds (77) and (78) have never been reported previously, while silvaglin A (47) was isolated for first time from Aglaia oligophyalla. Structure of the compounds were elucidated using various spectroscopic techniques such as GCMS, HRESIMS, FT-IR, 1D NMR and 2D NMR and comparison with the previous worked. In vitro investigation on the cytotoxic activitiy of isolates of both plants have been carried out towards human T-lymphoblastic (CEM-SS) and human cervical (HeLa) cancer cells. All the extracts of rhizomes Zingiber cassumunar showed no activity towards (CEM-SS) with IC50 values of > 30 μg/ml except for chloroform extract, which displayed IC50 value of 9.20 ± 0.02 μg/ml. Compounds (20) and (21) also exhibited moderate cytotoxic activity against CEM-SS cells with IC50 values 25.96 ± 0.94 and 28.34 ± 0.39 μg/ml, respectively. Meanwhile, all crude extracts from Zingiber cassumunar displayed no cytotoxicity activity against HeLa cells. However, all compounds isolated showed significant cytotoxic activity against HeLa cell line with IC50 values < 15 μg/ml. Most of the crude extracts from stem bark of Aglaia oligophylla showed no cytotoxic activity towards CEM-SS cells except for methanol extract with IC50 value 22.76 ± 0.08 μg/ml. All extracts from trunk also did not give any activity towards CEM-SS cells. Meanwhile, petroleum ether, chloroform and ethyl acetate extracts from stem bark of Aglaia oligophylla showed moderate cytotoxic activity with IC50 value less than 15 μg/ml against HeLa cells whilst methanol extract showed IC50 value of 22.93 ± 0.38. However, all extracts from trunk exhibit no cytotoxicity towards HeLa cells. Surprisingly, compounds (47), (77) and (78) showed interesting cytotoxic activity towards HeLa cancer cell line with IC50 value less than 15 μg/ml. Apart from the above activity, antimicrobial assay were also carried out on the isolates of the plants. Only certain extracts from Zingiber cassumunar and Aglaia oligophylla exhibit weak inhibition towards selected microbes and fungi while the rest were not active. Meanwhile, all extracts from both plants did not show any activity towards larvae of Aedes aegypti.